2020
DOI: 10.1111/irfi.12296
|View full text |Cite
|
Sign up to set email alerts
|

Corporate irresponsibility and stock price crash risk

Abstract: We investigate the impact of corporate irresponsibility on future stock price crash by employing a unique dataset of 1,529 penalties imposed on 411 United States (U.S.) firms, from 2003 to 2015. We provide robust evidence that the total amount of penalties (in U.S. dollars) imposed on firms are negatively associated with firm-specific future stock price crash risk. Our findings are consistent with the following view that imposition of penalties remove uncertainty about a particular firm's future, investors ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 90 publications
1
20
0
Order By: Relevance
“…In this manner, researchers have identified a number of factors that are associated with disclosure quality including the board of directors Nalukenge, 2020), audit committee Bananuka et al, 2018) and corporate governance quality (Nalukenge et al, 2018). Extending this work, academics have also explored the impact of good governance on sustainability reporting quality (Zaman et al, 2020a(Zaman et al, , 2020b. Researchers have found that corporate governance is a significant determinant of the extent of sustainability reporting (Jain and Jamali, 2016) and has the power and capacity to influence organisational decisions relating to materiality assessment disclosures.…”
Section: Determinants Of Materiality Assessment Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, researchers have identified a number of factors that are associated with disclosure quality including the board of directors Nalukenge, 2020), audit committee Bananuka et al, 2018) and corporate governance quality (Nalukenge et al, 2018). Extending this work, academics have also explored the impact of good governance on sustainability reporting quality (Zaman et al, 2020a(Zaman et al, , 2020b. Researchers have found that corporate governance is a significant determinant of the extent of sustainability reporting (Jain and Jamali, 2016) and has the power and capacity to influence organisational decisions relating to materiality assessment disclosures.…”
Section: Determinants Of Materiality Assessment Disclosuresmentioning
confidence: 99%
“…To demonstrate their commitment to sustainability, organisations undertake sustainability reporting, in which they provide stakeholders with information on the social, environmental and economic impact of their operations [1] (Global Reporting Initiative, 2021). While sustainability reporting is now a global norm (KPMG, 2017), critics complain that sustainability reporting is subject to managerial capture (O'Dwyer, 2003;Owen et al, 1997;Owen et al, 2000), whereby reporters primarily discuss positive performance (good news) while providing little to no information on negative performance (bad news) (Zaman et al, 2020a(Zaman et al, , 2020b. Such poor quality sustainability reports act as a façade hiding corporate hypocrisy (Cho et al, 2015;Howard et al, 2019;Maroun, 2018) and thereby preventing sustainability reporting from achieving its goal of promoting transparency and corporate sustainability accountability (Adams, 2004(Adams, , 2015Adams and Larrinaga-Gonz alez, 2007;Deegan and Gordon, 1996;Gray, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). In addition, monetary penalties (Zaman et al. , 2019), tight accounting standards (Abedifar et al.…”
Section: Macro-level Factorsmentioning
confidence: 99%
“…A study conducted in China found that increased environmental monitoring causes corporations to report more unfavorable news, lowering future stock price collapse risk (Zhang et al, 2021). In addition, monetary penalties (Zaman et al, 2019), tight accounting standards (Abedifar et al, 2019) and country-level governance (Song, 2015) have been shown to discourage withholding poor news and hence minimizing the probability of stock price crashes. Studies also demonstrate that country-level environmental policies (Yildiz and Karan, 2020) and the Securities and Exchange Commission regulations (Kubick and Lockhart, 2016) lower the likelihood of a firm's stock price drop.…”
Section: Political and Legal Factorsmentioning
confidence: 99%
“…Executives’ characteristic impact extends to affecting the degree of firm transparency and disclosure; Rahman et al (2021) investigated the corporate governance disclosure within the Bangladesh banking sector, and the results show the level of independent directors positively correlated with the governance disclosure, and more insider ownership lowers corporate governance efficiency. Kinateder et al (2021) found that boardroom gender diversity affects bank-specific credit risks (Hsu and Chen, 2015); specifically, it has been noted that three or more women on the board reduce the bank-specific credit risks (Zaman et al , 2020).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%